Evaluating the Effect of Three-Dimensional Visualization on Force Application and Performance Time during Robotics-Assisted Mitral Valve Repair. Issue 3 (May 2013) - Currie, Maria E.; Trejos, Ana Luisa; Rayman, Reiza; Chu, Michael W.A.; Patel, Rajni; Peters, Terry; Kiaii, Bob B.
Objective: The purpose of this study was to determine the effect of three-dimensional (3D) binocular, stereoscopic, and two-dimensional (2D) monocular visualization on robotics-assisted mitral valve annuloplasty versus conventional techniques in an ex vivo animal model. In addition, we sought to determine whether these effects were consistent between novices and experts in robotics-assisted cardiac surgery. Methods: A cardiac surgery test-bed was constructed to measure forces applied during mitral valve annuloplasty. Sutures were passed through the porcine mitral valve annulus by the participants with different levels of experience in robotics-assisted surgery and tied in place using both robotics-assisted and conventional surgery techniques. Results: The mean time for both the experts and the novices using 3D visualization was significantly less than that required using 2D vision (P < 0.001). However, there was no significant difference in the maximum force applied by the novices to the mitral valve during suturing (P = 0.7) and suture tying (P = 0.6) using either 2D or 3D visualization. The mean time required and forces applied by both the experts and the novices were significantly less using the conventional surgical technique than when using the robotic system with either 2D or 3D vision (P < 0.001). Conclusions: Despite high-quality binocular images, both the experts and the novices applied significantly more force to the cardiac tissue during 3D robotics-assisted mitral valve annuloplasty than during conventional open mitral valve annuloplasty. This finding suggests that 3D visualization does not fully compensate for the absence of haptic feedback in robotics-assisted cardiac surgery.